PENGARUH PAJANAN BISING TERHADAP GANGGUAN PENDENGARAN TIPE KONDUKTIF PEKERJA LAS DI HEAVY OIL OPERATION UNIT (HOOU) PT. CPI DURI, RIAU - Masnizar Tetryanto AZ; Usman M Tang; Nopriadi ' Nopriadi (Program Pascasarjana Universitas Riau, 2014)
PT Chevron Pacific Indonesia is one of the workplaces that are the province of Riau . Inmany mechanical construction and use of welding machines and grinding machines thatcan cause adverse effects to human health and the environment. This study aims todetermine the effect of noise exposure received by workers welding within 8 hours ofwork on the type of conductive hearing loss . This study is an observational study withcross sectional design with a sample of workers studied sebanyak138 welding (welder).Noise data obtained using the Sound Level Meter (SLM ) and the examination of thetype of conductive hearing loss qualitative ( classical ) using garputala 512Hz. Theresults showed that no significant influence of age , years of service and acceptablenoise exposure of workers welding on the type of conductive hearing loss ( p-value ≥0.010 ) and found a significant effect of consistency ( compliance ) use ear protectivedevices ( APT ) the type of conductive hearing loss ( p - value = 0.000 ) . in the regionof Heavy Oil Infrastructure Maintenance Unit Operation PT. Chevron PacificIndonesia ( IM - HOOU CPI ) Duri. The companyis expected toprovide training on theuse ofear protective devices (APT) on a regular basisso asto function optimally and thecompany is also expected to implementa hearing conservation program that includesnoise surveys, engineering controls, hearing protection, audio metric examinationperiodically, training programs, program evaluation and audit.